2017
DOI: 10.1016/bs.mie.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation DNA Curtains for Single-Molecule Studies of Homologous Recombination

Abstract: Homologous recombination (HR) is a universally conserved DNA double-strand break repair pathway. Single-molecule fluorescence imaging approaches have revealed new mechanistic insights into nearly all aspects of HR. These methods are especially suited for studying protein complexes because multicolor fluorescent imaging can parse out subassemblies and transient intermediates that associate with the DNA substrates on the millisecond to hour timescales. However, acquiring single-molecule datasets remains challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…The ladder of bands further indicated that multiple Gam dimers can load on the substrate, as has been observed for the eukaryotic Ku complex. Next, we employed high-throughput single-molecule DNA curtains to image MuGam as it interacts with the DNA substrate (30,31). In this assay, thousands of individual DNA molecules (∼48.5 kb long, derived from λ-phage DNA) are organized at microfabricated chromium barriers and visualized by total internal reflection fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ladder of bands further indicated that multiple Gam dimers can load on the substrate, as has been observed for the eukaryotic Ku complex. Next, we employed high-throughput single-molecule DNA curtains to image MuGam as it interacts with the DNA substrate (30,31). In this assay, thousands of individual DNA molecules (∼48.5 kb long, derived from λ-phage DNA) are organized at microfabricated chromium barriers and visualized by total internal reflection fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…DNA curtains were assembled on microfabricated microscope slides, as described previously (30,31). All single-molecule data were collected at 37°C in imaging buffer [40 mM Tris·HCl (pH 8.0), 2 mM MgCl2, 1 mM ATP, 1 mM DTT, 0.2 mg·mL −1 BSA] on a Nikon Ti-E microscope in a prism total internal reflection fluorescence configuration.…”
Section: Methodsmentioning
confidence: 99%
“…We established a single-molecule DNA curtains assay to image the role of RPA during DNA resection (Figure 1). In this assay, BLM helicase and the nucleases EXO1 or DNA2 are imaged on 48.5 kb-long DNA molecules that are organized on the surface of a lipid-coated microfluidic flowcell (Gallardo et al, 2015;Soniat et al, 2017). One end of the DNA substrate is biotinylated and tethered to streptavidin deposited on the lipid bilayer.…”
Section: Mechanism Of Blm/exo1-mediated Dna Resectionmentioning
confidence: 99%
“…We examined Mlh1-Pms1 diffusion on doubletethered DNA curtains (Figure 2A-B). In this assay, a 48.5 kb-long DNA substrate is extended over a fluid lipid bilayer between two microfabricated chromium barriers (51,60,61). The lipid bilayer provides a biomimetic surface that passivates the flowcell surface from non-specific adsorption by DNA-binding proteins.…”
Section: Idrs Promote Facilitated Diffusion On Both Naked and Nucleosmentioning
confidence: 99%